PENGARUH PENDAPATAN ASLI DAERAH, DBH, DAU, DAK TERHADAP BELANJA MODAL - Tryas Chasbiandani; Rafrini Amyulianthy; Anisa May (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2022)
The purpose of this study is determine the effect of fund local own revenue, sharing-revenue fund, general allocation funds and special allocation funds on capital expenditures. Sharing-revenue funds, general allocation funds and special allocation funds are equalization fund and a unit that cannot be separated, but due to different allocations, the authors describe the equalization funds. The data used is panel data which includes data on growth of fund local own revenue, growth in sharing-revenue fund, general allocation funds and special allocation funds as independent variables, and capital expenditure as the dependent variable in several districts and cities in West Java province during the 2014-2018 research period. The method of analysis used is multiple linear regression using the Eviews-11 program. The results showed that the growth of local own revenue, the growth of sharing-revenue funds, the growth of general allocation funds had a significant effect on capital spending. Meanwhile, the growth of special allocation funds has no effect on capital expenditure, but simultaneously the equalization fund have an effect on capital spending. Keywords: Fund Local Own Revenue (PAD), Sharing-revenue Fund (DBH), General Allocation Fund (DAU), Special Allocation Fund (DAK), Capital Expenditure (Belanja Modal)